Uma estratégia computacional para a análise técnica de pedidos de ressarcimento de danos a consumidores - Tavares, Carlos Eduardo (2008)
The new Brazilian electric sector model establishes the basis for the relationship amongst the three partners: supplier, consumer and regulatory agencies. The utilities are to deliver electric energy so as to satisfy safety and trustworthy in accordance with the regulation. The consumer assumes the commitment of the attendance of determinations imposed by adhesion contracts. The State, represented by the regulatory agencies, remains the task to establish rules and standards of services. Within this area emerges a controversial subject related to Refunding Request for Damages . This pursuing has for goal the identification of the real cause of events and the emission of conclusive reports on the consistency or not of the requests of damage compensation suffered by the consumer. Nowadays, the processes follow simple procedures, normally based on technician assistance survey that suggests a possible origin of damage. In this way, utilities, many times, opts to paying the consumer prejudices to avoid disagreement with them. However, the dissemination of the knowledge of the consumer rights has led to an alarming increase in the total price paid for it. The aggravating circumstance is that many utilities do not have records of electric magnitudes associated with the majority of the occurrences. Consequently, the agreement or contestation of the request under analysis becomes extremely difficult, remaining to the utilities just the verification of the causal nexus and the supposition of severity of the impacts of the occurred event on the complained products. Due to the increasing number of refunding requests, the high amount of financial resources involved and the necessity of having a technical and impartial approach to help the final decision, this thesis deals with a computational method which has been developed and implemented to avoid the consumer dissatisfaction.